PENGARUH DISIPLIN KERJA, STRES KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWA - Aditya, Yudi Putra; Rauly Sijabat; Noni Setyorini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this study was to analyze the effect of work discipline on employee performance, analyze the effect of work stress on employee performance, and analyze the effect of work motivation on employee performance. The object of this research is at Bank BRI Cabang Pattimura Semarang. The method in this study is a survey research method with a quantitative approach. The population in this study were all employees at Bank BRI Cabang Pattimura Semarang. The number of samples in this study were 80 respondents who were obtained using saturated sampling, namely the sampling technique when all members of the population are used as samples. Methods of data collection through questionnaires and data analysis using SPSS which includes validity test, reliability test, classic assumption test, multiple linear regression analysis, hypothesis testing using t test, R² test. The results showed that the independent variables, namely work discipline (X1), work stress (X2), work motivation (X3) have a positive and significant effect on employee performance (Y) partially or simultaneously (together). Based on the coefficient of determination of 0.565, which means that the variables of work discipline (X1), work stress (X2), and work motivation (X3) are simultaneously able to explain the employee performance variable (Y) of 56.5%. The remaining 43.5% of employee performance (Y) is explained by other variables not included in this study.